2018
DOI: 10.1007/s00405-018-4922-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards an in vitro fibrogenesis model of human vocal fold scarring

Abstract: BackgroundVocal fold (VF) scarring remains a therapeutic dilemma and challenge in modern laryngology. To facilitate corresponding research, we aimed to establish an in vitro fibrogenesis model employing human VF fibroblasts (hVFF) and the principles of macromolecular crowding (MMC).MethodsFibrogenesis was promoted by addition of transforming growth factor-β1 to standard medium and medium containing inert macromolecules (MMC). Hepatocyte growth factor (HGF) and Botox type A were tested for their antifibrotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Branco et al evaluated the myofibroblast profile isolated from normal and scarred human VF and suggested that VF fibroblast treated with TGFβ1 (myofibroblasts) appear to have similar phenotypic characteristics but different genotypic behavior compared to VF fibroblasts isolated from human VF scars [61]. Graupp et al established a laryngeal fibrogenesis model employing human VF fibroblasts based on the principle of the macromolecular crowding [62]. These excellent recent in vitro VF fibroblast models would accelerate the development of the novel treatment strategy for VF scars.…”
Section: Histopathology Of Vf Scarring In Vivo and In Vitromentioning
confidence: 99%
“…Branco et al evaluated the myofibroblast profile isolated from normal and scarred human VF and suggested that VF fibroblast treated with TGFβ1 (myofibroblasts) appear to have similar phenotypic characteristics but different genotypic behavior compared to VF fibroblasts isolated from human VF scars [61]. Graupp et al established a laryngeal fibrogenesis model employing human VF fibroblasts based on the principle of the macromolecular crowding [62]. These excellent recent in vitro VF fibroblast models would accelerate the development of the novel treatment strategy for VF scars.…”
Section: Histopathology Of Vf Scarring In Vivo and In Vitromentioning
confidence: 99%
“…Since the hallmark of fibrosis is the deposition of excessive amounts of collagen by activated fibroblasts (i.e., myofibroblasts) ( 29 , 30 ), MMC might be a helpful tool for cellular drug screening, as it markedly shortens the culture time at which collagen deposition becomes visible. Indeed, MMC has been used for this purpose ( 5 , 6 , 31 , 32 ), which is also known as the Scar-in-a-Jar system.…”
Section: Introductionmentioning
confidence: 99%
“…They are Ficoll PM 70 (Fc70), Ficoll PM 400 (Fc400), a mixture of Ficoll 70 and 400 (Fc70/400), polyvinylpyrrolidone 40 (PVP40), polyvinylpyrrolidone 360 (PVP360), neutral dextran 670 (ND670), dextran sulfate 10, dextran sulfate 500 (DxS500), carrageenan (CR), and polysodium-4-styrene sulfonate. Human fibroblasts used are WI-38 cells (embryonic lung fibroblasts) ( 3 , 4 , 6 , 31 , 38 ), WS-1 cells (embryonic dermal fibroblasts) ( 38 , 39 ), adult dermal fibroblasts ( 37 , 40 ), adult corneal fibroblasts (keratocytes) ( 34 36 ) and immortalized adult vocal fold fibroblasts ( 32 ). However, it should be stressed that it is the myofibroblast that is mainly responsible for the collagen deposition seen in fibrosis, not the fibroblast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other more experimental treatments such as administration of basic Fibroblast Growth Factor (bFGF) [9,10] or Hepatocyte Growth Factor (HGF) [11][12][13][14] have shown encouraging effects in vitro or in vivo on animals. However, only one phase I/II clinical trial assessed the safety and effectiveness of intracordal injection of a recombinant human HGF in patients with vocal fold scar or sulcus [15].…”
Section: Introductionmentioning
confidence: 99%